2017
DOI: 10.1111/hepr.12994
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of semiquantitative PCR‐Invader assay for selecting candidates for daclatasvir plus asunaprevir combination therapy among patients with hepatitis C virus genotype 1b

Abstract: Treatment efficacy of DCV + ASV was extremely high among patients who were non-positive for NS5A RAVs on SQ-PI, especially for patients with negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similarly, a previous clinical trial using SOF/LDV resulted in a high SVR rate for genotype 1 HCV-infected adolescents, including patients with NS5A RAVs (16). Concerning RAV detection, Honda et al reported that the semiquantitative polymerase chain reaction (PCR)-Invader assay is a highly sensitive method for determining the presence of pretreatment minor NS5A variants (21). Further studies on the relationship between DAA efficacy and RAVs in children and the optimal method for determining the presence of RAVs are needed.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a previous clinical trial using SOF/LDV resulted in a high SVR rate for genotype 1 HCV-infected adolescents, including patients with NS5A RAVs (16). Concerning RAV detection, Honda et al reported that the semiquantitative polymerase chain reaction (PCR)-Invader assay is a highly sensitive method for determining the presence of pretreatment minor NS5A variants (21). Further studies on the relationship between DAA efficacy and RAVs in children and the optimal method for determining the presence of RAVs are needed.…”
Section: Discussionmentioning
confidence: 98%
“…RAS detection in the NS5A region at baseline was performed by Invader assay (BML, Inc., Saitama, Japan) [13,14]. The targeted mutations included L31F/M/V and Y93H in the NS5A region.…”
Section: Invader Assaymentioning
confidence: 99%